Understanding the history of women's lives in Zanzibar through song and story: a gendered perspective - Clacherty, Bronwen (College of Music, 2021)
This dissertation and the accompanying performance explore women's history through the song genre dandaro learned from women's singing groups in present-day Zanzibar. The study aims to show that songs, a part of oral tradition, are an effective way of adding to the minimal understanding we have of women's lives in Zanzibar and the Indian Ocean. The dissertation transcribes both the lyrics and the music of the dandaro songs and analyses them in relation to theoretical perspectives on archive and gender realities, as well as in the context of the history of Zanzibar. It also describes how and why I created a performance that reflected both the journey of my research as well as what the women and men I met shared with me. The dissertation and performance form a whole and the performed work is incorporated into the dissertation to show how the performance deepened the approach to the theory and data and vice versa. This study of dandaro songs reveals the existence of a transgenerational archive of information that preserves and transmits the image of strong womanhood and woman's agency, where women subvert gender norms and express their solidarity with each other.